The Importance of Mother Tongue and Children's Literature in Primary School - Fozilov Jakhongir Ibrokhimovich; Abduraxmonova Mohinur Furqatjon qizi (Genius Journals, 2022)
In the following points, we provide information about the internal potential of students' native language, its diversity, and the current status of the development of our native language.
Keywords: Mother tongue; literature; state language; speech